Sustainable framing systems for food security in Saudi Arabia: the synergistic role of agriculture mechanization, farm structure, gender dynamics, and resource optimization - Mabrouk, Fatma; Mashaal, Ahmed A.; Eliw, Moataz; Iqbal, Muhammad Amjed; Samie, Abdus; Abbas, Azhar (Frontiers in Sustainable Food Systems, 2025)
IntroductionClimate change is a serious threat to the global food production systems contributing to inflated food prices, especially in countries with scarce resources and lower share of domestic food production in their food security. Sustainable food systems can ensure food security and mitigate the effects of climate change on the natural ecosystems in these countries. Saudi Arabia, which is characterized by an arid climate and increasing climate vulnerability, faces inimitable challenges in achieving food security in 21st century. The country’s severe climatic conditions, including limited arable land and small freshwater resources, pose a substantial barrier to achieving Vision 2030 goals of economic diversification and reducing reliance on foreign foods. Thus, promoting sustainable food system approach can help Saudi Arabia achieve self-reliance on food production and ensure food security. Thus, the primary objective of this study is to explore the synergistic effect of agricultural mechanization, farm structure, gender dynamics, resource optimization, and agricultural value addition on sustainability of food systems and food security in Saudi Arabia.MethodologyThe autoregressive distributed lag bounds test and Granger Causality were used to analyze data from 1991 to 2019. Two different unit root tests augmented Dickey-Fuller and Phillips-Perron were applied to justify the integrated order of all variables.ResultsThe results showed that farm structure, population density, agriculture value addition, and male and female participation significantly affected households’ food security in the short and long run. A 1% rise in agricultural value addition increases calorie supply by 653.3 kcal per day per capita. Similarly, for a 1 unit increase in farm structure, calorie availability in the country increased by almost 673 kcal per day per capita. Moreover, a one-unit increase in population density reduced calorie supply by 433.3 kcal per day per capita. Farm mechanization and resource-use efficiency significantly affect food security only in the short run.ConclusionThe development of women-led agribusiness enterprises will strengthen Saudi Arabia’s agricultural sector while supporting the national gender equality objectives established in Vision 2030.